Risk factors for severity of breast cancer-related lymphedema - Amirhossein Bahanesteh; Hossein Yarmohammadi; Sina Shahshenas; Davood Dalil; Masood Soltanipur; Hamidreza Taheri; Zahra Sheikhi (Radiation Oncology)
Abstract Introduction Breast cancer-related lymphedema (BCRL) is a debilitating condition that affects a significant proportion of breast cancer survivors, profoundly impacting their quality of life. While many studies have investigated the risk factors for BCRL occurrence, the determinants of its severity remain underexplored. Methods This retrospective observational study evaluated the risk factors associated with BCRL severity among patients treated at the Motamed Cancer Institute, Tehran, Iran. Female patients with unilateral BCRL aged 25–75 years were included. Data were collected over a 10-year period and analyzed for demographic, clinical, and pathological variables. Lymphedema severity was assessed using established clinical staging criteria and categorized into early-stage (stages 1 and 2a) and advanced-stage (stages 2b and 3) groups. Also, presence of fibrosis and non-pitting edema were other indicators of BCRL severity. Statistical analyses included univariate and multivariate logistic regression to identify predictors of advanced-stage BCRL. Results A total of 500 participants were analyzed, with a mean age of 41.16 ± 10.20 years and BMI of 28.72 ± 4.78 kg/m². Advanced-stage BCRL was significantly associated with older age (p = 0.00), higher number of excised lymph nodes (p = 0.04), and radiotherapy (p = 0.00). Multivariate analysis identified radiotherapy as the strongest independent predictor of advanced-stage BCRL (OR: 2.12, 95% CI: 1.22–3.67, p = 0.007). Other variables, including tumor grade, molecular subtypes, and type of surgery, did not independently predict BCRL severity. Conclusion Advanced-stage BCRL is influenced by multiple factors, particularly radiotherapy and the extent of lymph node dissection. These findings underscore the importance of strategies to mitigate risk among breast cancer survivors, especially those undergoing radiotherapy. Further research is warranted to explore targeted interventions for reducing BCRL severity.